1990
DOI: 10.1016/0035-9203(90)90299-t
|View full text |Cite
|
Sign up to set email alerts
|

The Imo State (Nigeria) Drinking Water Supply and Sanitation Project, 1. Description of the project, evaluation methods, and impact on intervening variables

Abstract: A health impact evaluation was conducted in conjunction with the Imo State Drinking Water Supply and Sanitation Project in Nigeria. The project consisted of a package of water supply, sanitation, and health and hygiene education given by village-based workers. The evaluation was a quasi-experimental study covering pre-, peri- and post-intervention periods. Data were collected from 3 intervention and 2 control villages. Baseline surveys indicated that the intervention and control areas were similar with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 5 publications
3
19
1
Order By: Relevance
“…In contrast to previous research (Blum et al 1990;Rijal et al 1998) the level of fecal contamination in water from the household containers was lower than from the drinking water sources, either wells or taps, indicating that there is no fresh contamination occurring in the households. The lower levels in the household may be due to natural die-off of bacteria over time, or due to bacterial properties of the brass containers that are used for drinking water storage in the home.…”
Section: Fecal Contaminationcontrasting
confidence: 91%
“…In contrast to previous research (Blum et al 1990;Rijal et al 1998) the level of fecal contamination in water from the household containers was lower than from the drinking water sources, either wells or taps, indicating that there is no fresh contamination occurring in the households. The lower levels in the household may be due to natural die-off of bacteria over time, or due to bacterial properties of the brass containers that are used for drinking water storage in the home.…”
Section: Fecal Contaminationcontrasting
confidence: 91%
“…Lack of proper hygiene practices, such as cleaning of drinking water storage vessels and dipping utensils used to remove drinking water from storage vessels, and washing of hands, as well as exposure of drinking water stored in open-top containers to dust and fomites has been shown to contribute to decreased microbial quality of drinking water, in this study as well as in the literature (Blum et al, 1990;Tuttle et al, 1995;Trevett et al, 2005;Onabulo et al, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, a high proportion of children were observed to collect and serve water, and it is reasonable to assume that children will take less care to avoid handwater contact. Several other studies have reported similar findings linking hand contact to water quality deterioration (Feachem et al 1978;Blum et al 1990;Pinfold 1990a;Hoque et al 1995;Roberts et al 2001). We asked women before/ after which activities they used soap to wash their hands in our Honduran research (Trevett 2003).…”
Section: Legendsupporting
confidence: 51%
“…However, the strength or validity of these arguments is questionable. For example, the deterioration of drinking water quality between collection and consumption has been shown to be a common and widespread problem (Hammad & Dirar 1982;Blum et al 1990;Empereur-Bissonnet et al 1992;Swerdlow et al 1992;Kaltenthaler et al 1996;Genthe et al 1997;Hoque et al 1999;Roberts et al 2001;Trevett et al 2004). The epidemiological significance therefore may be much greater than previously believed.…”
Section: Two Opposing Viewpointsmentioning
confidence: 86%